Dialektika Kepercayaan Lokal dengan Islam dalam Simbolisme Arsitektur (Studi Atap Rumah Mayarakat Baringeng di Kabupaten Soppeng) - Selviana, Selviana; Musafir Pababbari; Dewi Anggariani (CV. ULIL ALBAB CORP, 2025)
This study analyzes the roofs of Baringeng houses as a reflection of the dialectic between local beliefs and Islam and its implications for socio-religious life. The focus of the study includes: the determination of house roofs, the interaction between traditional values and Islamic teachings, and their impact on community life. This study uses qualitative methods with an ethnographic and theological approach. Data was obtained through observation, interviews with village officials, religious leaders, builders, and the community, as well as document studies. The analysis was carried out through the stages of collection, reduction, presentation, and conclusion.The results of the study show that the direction and shape of the roof are still influenced by traditional customs. The west direction is chosen because it corresponds to the qibla and is believed to bring blessings, while the timpa laja shape reflects social status. This tradition demonstrates the harmony between customs and Islam, strengthening both cultural and religious identity. The implications are that, socially, it strengthens solidarity and the visual unity of the settlement, while religiously, it facilitates the arrangement of worship spaces in accordance with the qibla.